Bariatric surgery in adolescents: a prospective randomized controlled trial comparing laparoscopic gastric banding to combined lifestyle interventions in adolescents with severe obesity (BASIC trial) - Y. G. M. Roebroek; G. F. Paulus; E. G. A. H. van Mil; A. C. E. Vreugdenhil; B. Winkens; C. Nederkoorn; C. D. A. Stehouwer; J. W. M. Greve; N. D. Bouvy; L. W. E. van Heurn (BMC, 2019)
Abstract Background Obesity in children and adolescents is an increasing problem associated with multiple co-morbidities including metabolic and endocrine changes, cardiovascular abnormalities, and impaired quality of life. Combined lifestyle interventions are the current standard treatment for severe obesity in children. However, the medium- and long-term results of these interventions are relatively poor. Bariatric surgery shows substantial weight loss and health improvement in adults and retrospective studies in adolescents show similar outcomes. However, well-designed prospective studies in this young age group are rare. Our objectives are to determine whether combining surgery with lifestyle interventions in severely obese adolescents leads to a significant additional weight reduction compared to lifestyle interventions solely, and to assess its effect on obesity-associated co-morbidities in a prospective randomized controlled setting. Methods Patients aged 14-16 years with sex- and age-adjusted BMI > 40 kg/m2 (or > 35 kg/m2 with comorbidity) and failure to achieve weight reduction > 5% during at least one year of combined lifestyle interventions are included in this trial. Randomization determines whether laparoscopic adjustable gastric banding will be added to combined lifestyle intervention throughout the trial period. Sixty children will be included in this trial. Follow-up visits are planned at 6 months, 1,2 and 3 years. Primary endpoints are percentage of total weight loss, and change of BMI. Secondary endpoints include body composition, pubertal development, metabolic and endocrine changes, inflammatory status, cardiovascular abnormalities, non-alcoholic steatohepatitis, quality of life and changes in behaviour. Discussion This randomized controlled trial is designed to provide important information about the safety and efficacy of laparoscopic adjustable gastric banding treatment in severely obese adolescents with unsuccessful combined lifestyle interventions. The reversibility of this surgical procedure forms a strong argument to decide for gastric banding over other surgical procedures, since bariatric surgery in adolescents is still in its infancy. Trial registration The BASIC trial is registered in the register of ClinicalTrials.gov since July 2010, Identifier: NCT01172899